Economic Cost Model of Options to Global Sulphur Cap considering Speed Differentiation - Daozheng Huang; Yimin Hua (Discrete Dynamics in Nature and Society)
The 2020 global sulphur cap has been implemented to reduce the sulphur emission of the maritime transportation industry. It is a huge challenge for the ship owners to select a proper strategy to comply with the regulation. This study analyzes the economic costs of measures to comply with the sulphur cap including switching to low sulphur fuel oil (LSFO) and scrubbers. Meanwhile, considering the influence of the speed optimization on the voyage cost, an economic cost model of the LSFO method is combined with speed differentiation inside and outside the Sulphur Emission Control Area (SECA). The route from Shanghai to Los Angeles is set as a case study. The optimal speeds inside and outside the SECA are calibrated. Then, the economic costs of both methods are calculated and compared. The results show that the speed differentiation strategy can reduce the economic cost of the LSFO method and thus reduce its cost disadvantage over scrubbers. In addition, a low discount rate would benefit the scrubber option based on sensitivity analysis.